An InP-based heterodimensional Schottky diode for terahertz detection - 闻孺铭 孙浩 滕腾 李凌云 孙晓玮 (Journal of semiconductors, 2012)
We present an InP-based heterodimensional Schottky diode（HDSD）,which has so far never been reported in the literature.Compared to a GaAs-based HDSD,the InP-based HDSD is expected to have better high frequency performance and operational conditions resulting from its higher mobility and concentration of 2D electron gas（2DEG） as well as its smaller Schottky barrier height.The cutoff frequency of the InP-based HDSD obtained by the AC measurement is more than 500 GHz,which shows its potential application in terahertz detection.